P11.11 High rates of co-occurring sexually transmissible infections among men who have sex with men attending high-caseload general practice and sexual health services in victoria. (13th September 2015) - Leitinger, D; Wilkinson, A; Bartnik, N; Fairley, C; Tee, BK; Roth, N; Leslie, D; El-Hayek, C; Hellard, M; Stoové, M
Abstract : Introduction: Sexually transmissible infection (STI) screening and treatment is a health priority for gay, bisexual and other men who have sex with men (GBM). Current Australian guidelines recommend frequent syphilis serology and screening for pharyngeal, anorectal and urogenital chlamydia and gonorrhoea infection, in addition to routine HIV testing. However, evidence from recent community surveys that many Australian GBM access only some of these tests suggests concurrent infections may remain undetected. Methods: To better understand the epidemiology of co-occurring curative STIs, we calculated the proportion of positive tests for one or more STI among GBM attending two sexual health services and two gay-friendly high-caseload general practices in Victoria between 2007 and 2013. Among positive tests for chlamydia or gonorrhoea, we calculated the proportion positive at multiple anatomical sites. We examined demographic and risk behaviour associations with co-occurring STIs and positivity at multiple anatomical sites using adjusted logistic regression. Results: There were 70977 test events between 2007 and 2013; 8316 (11.7%) were positive for at least one STI and of these, 792 (9.5%) were positive for more than one STI. Younger age (16–29 years) (aOR = 1.7, 95% CI = 1.1–2.7), being HIV-positive (aOR = 2.2, 95% CI = 1.5–3.1) and reporting inconsistent condom use (aOR = 1.3, 95% CI = 1.0–1.6) were associated with testing positive for co-occurring infections. Of 7584 test events positive for chlamydia or gonorrhoea, 1028 (13.6%) were positive for either infection at multiple sites. Being aged 16–29 (aOR = 2.9, 95% CI = 1.8–4.6) or 30–39 (aOR = 2.4, 95% CI = 1.5–3.9) was associated with testing positive for either infection at multiple sites. Conclusion: The high prevalence of co-occurring STIs and infection at multiple anatomical sites supports national guidelines for frequent comprehensive testing for GBM. These results support the promotion of comprehensive STI testing for GBM, including in lower-caseload settings alongside taking appropriate sexual histories, and underline the importance of structural efforts to maximise access to comprehensive testing for GBM. Disclosure of interest statement: All authors have no conflicts to declare. The authors gratefully acknowledge patients and participating clinics and laboratories for the ongoing data contribution. The authors acknowledge Drs Norm Roth and BK Tee for their ongoing support of surveillance work at the Burnet Institute. The Victorian Department of Health funds ongoing surveillance projects within the Burnet Institute. The authors would like to acknowledge the NHMRC who provide funding to Anna Wilkinson as a public health scholarship recipient. Mark Stoové is supported by an NHMRC Career Development Fellowship. The authors gratefully acknowledge the contribution to this work of Victorian Operational Infrastructure Support Program received by the Burnet Institute.